Hubungan antara Faktor Pengetahuan Ibu, Sosial Budaya dan Informasi Petugas Kesehatan dalam Praktik Pemberian MP-ASI Dini dengan Kejadian Diare Akut pada Bayi - Salsabila Ardhani; Roro RUkmi WIndi P; Agustyas Tjiptaningrum (CV. Jasa Sukses Abadi, 2020)
Diarrhea is one of the main causes of illness and death in childhood in developing countries. Diarrhea is caused by various factors one of which is the practice of early giving weaning food. The purpose of this study was to determine the relationship between the factors that influence the practice of giving early weaning food with the incidence of diarrhea in infants aged 0-6 months in Kemiling Health Center. This type of research is analytic observational research with cross sectional design, the sample in this study were all infants aged 0-6 months who sought treatment in Kemiling Health Center in February-March 2018 with consecutive sampling techniques and analyzed using chi square. The results show that there was a significant relationship between mother’s knowledge about early giving weaning food with the incidence of acute diarrhea in infants with a p-value of 0.009 (<α = 0.05), a significant relationship between socio-culture and the provision of early giving weaning food with the incidence of acute diarrhea in infants with a p-value of 0.003 (<α = 0.05 ), and a significant relationship between health care worker information about early giving weaning food and the incidence of acute diarrhea in infants with a p-value of 0.001 (<α = 0.05). There is a significant relationship between mother’s knowledge factor, socio culture factor, and health care worker information factor that influence the practice of early giving weaning food and diarrhea in infants aged 0-6 months at Kemiling Health Center in Bandar Lampung City.